An Assessment of the Capability of ICT Education in Bicol University Polangui Campus, Polangui, Albay, Philippines: A Determinant to its Sustainability - RiÃƒÂ±on, Bernardita B; Belchez, Nelly B (School of Business and Management Institut Teknologi Bandung, 2012)
The 21st Century poses an urgent need for the integration of ICT in classroom instruction. Education is a lifelong process therefore access to information anytime, anywhere is imperative. We need literates to meet the challenges of illiteracy and poverty and bring about the cost reduction of education,Â Â improve the quality and effectiveness of teaching (wikieducator,n.d.). This paper intends to present the results of an assessment on the capability of ICT education where its sustainability largely depends upon it. Specifically, it aimed to determine the profile of the facilities, faculty readiness in ICT literacy, related researches, budgetary allocation for facilities and linkages with non-government and government agencies likewise the level of capability of ICT education was assessed. Findings revealed that the school has the capability to sustain ICT education. In this study, the researchers arrived at the conclusion that capable and sustainable ICT education would produce ICT literates individuals who would meet the challenges of digital world. Keywords:ICT,Capability,Sustainability, New Literacy, Teachersâ€™ Readiness